2004
DOI: 10.1038/sj.leu.2403330
|View full text |Cite
|
Sign up to set email alerts
|

Preferential expression of the vasoactive intestinal peptide (VIP) receptor VPAC1 in human cord blood-derived CD34+CD38− cells: possible role of VIP as a growth-promoting factor for hematopoietic stem/progenitor cells

Abstract: Primitive hematopoietic progenitor cells such as severe combined immunodeficiency-repopulating cells and long-term culture-initiating cells are enriched in CD34 þ CD38 À cells derived from various stem cell sources. In this study, to elucidate the features of such primitive cells at the molecular level, we tried to isolate genes that were preferentially expressed in umbilical cord blood (CB)-derived CD34 þ CD38À cells by subtractive hybridization. The gene for VPAC1 receptor, a receptor for the neuropeptide va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Monocytes and T cells also constitutively express VPAC 1 , whereas VPAC 2 is inducible by specific cell activation (35)(36)(37). VPAC 1 receptor has also been preferentially detected in CD34ϩ,CD38Ϫ primitive hematopoietic stem cells (38). All of these data indicated that in several systems, VPAC 2 could represent a marker of cell activation or differentiation, explaining its predominant presence in RA FLS or TNF␣-treated OA FLS.…”
Section: Discussionmentioning
confidence: 89%
“…Monocytes and T cells also constitutively express VPAC 1 , whereas VPAC 2 is inducible by specific cell activation (35)(36)(37). VPAC 1 receptor has also been preferentially detected in CD34ϩ,CD38Ϫ primitive hematopoietic stem cells (38). All of these data indicated that in several systems, VPAC 2 could represent a marker of cell activation or differentiation, explaining its predominant presence in RA FLS or TNF␣-treated OA FLS.…”
Section: Discussionmentioning
confidence: 89%
“…Human hematopoietic stem cells that are enriched for CD34 + cells derived from either bone marrow or cord blood (CB) have been shown to predominately express VPAC1 verses VPAC2 as assessed by semi-quantitative PCR, subtractive hybridization and western analysis [54,55] . Also, the immature, non-dividing CD34 +…”
Section: Vpac Receptor Expression Profile In Hematopoiesismentioning
confidence: 99%
“…The signaling induced by VPAC1 due to added VIP ligand (10 -9 mol/L) to these hematopoietic stem precursor cells showed a synergic effect on myeloid and mixed colony growth of CD34 + CB cells with little to no detectable effect on BM cells in the presence, but not absence of three early cytokines, FLT3 ligand, stem cell factor (STF) and thrombopoietin (TPO) [55] . Another study confirmed high levels of VPAC1 mRNA in BM cells, but exogenously added VIP (10 -13 to 10 -7 mol/L) instead suppressed erythroid and myeloid colony growth, with a concomitant increase in transforming growth factor (TGF)-β and tumor necrosis factor (TNF)-α from an unidentified stromal cell type (possibly macrophages) [54] .…”
Section: Cd38mentioning
confidence: 99%
“…(4,16,32) in which HCMV also reactivates with greater frequency (26,33,40,43,51,80). VIP receptors are expressed on progenitors of neuronal, hepatic, retinal pigment epithelial, and hematopoietic cells (6,7,35,82). On the basis of this information, VIP was further studied in the HCMV reactivation model.…”
Section: Cells and Virusesmentioning
confidence: 99%